Effectiveness and cost-effectiveness of community-based TB screening algorithms using computer-aided detection (CAD) technology alone compared with CAD combined with point-of-care C reactive protein testing in Lesotho and South Africa: protocol for a paired screen-positive trial - Fabrizio Tediosi; Klaus Reither; Bram van Ginneken; Alastair van Heerden; Tinne Gils; Lutgarde Lynen; Josephine Muhairwe; Alfred Kipyegon Keter; Aita Signorell; Rediet Fikru Gebresenbet; Irene Ayakaka; Thomas Zoller; et al. (BMJ Open)
Introduction Tuberculosis (TB) remains a significant public health challenge in many African communities, where underreporting and underdiagnosis are prevalent due to barriers in accessing care and inadequate diagnostic tools. This is particularly concerning in hard-to-reach areas with a high burden of TB/HIV co-infection, where missed or delayed diagnoses exacerbate disease transmission, increase mortality and lead to severe economic and health consequences. To address these challenges, it is crucial to evaluate innovative, cost-effective, community-based screening strategies that can improve early detection and linkage to care.Methods and analysis We conduct a prospective, community-based, diagnostic, pragmatic trial in communities of the Butha Buthe District in Lesotho and the Greater Edendale area of Msunduzi Municipality, KwaZulu-Natal in South Africa to compare two strategies for population-based TB screening: computer-aided detection (CAD) technology alone (CAD4TBv7 approach) versus CAD combined with point-of-care C reactive protein (CRP) testing (CAD4TBv7-CRP approach). Following a chest X-ray, CAD produces an abnormality score, which indicates the likelihood of TB. Score thresholds informing the screening logic for both approaches were determined based on the WHO’s target product profile for a TB screening test. CAD scores above a threshold prespecified for the CAD4TBv7 approach indicate confirmatory testing for TB (Xpert MTB/RIF Ultra). For the CAD4TBv7-CRP approach, a CAD score within a predefined window requires the conduct of the second screening test, CRP, while a score above the respective upper threshold is followed by Xpert MTB/RIF Ultra. A CRP result above the selected cut-off also requires a confirmatory TB test. Participants with CAD scores below the (lower) threshold and those with CRP levels below the cut-off are considered screen-negative. The trial aims to compare the yield of detected TB cases and cost-effectiveness between two screening approaches by applying a paired screen-positive design. 20 000 adult participants will be enrolled and will receive a posterior anterior digital chest X-ray which is analysed by CAD software.Ethics and dissemination The protocol was approved by National Health Research Ethics Committee in Lesotho (NH-REC, ID52-2022), the Human Sciences Research Council Research Ethics Committee (HSRC REC, REC 2/23/09/20) and the Provincial Health Research Committee of the Department of Health of KwaZulu-Natal (KZ_202209_022) in South Africa and from the Swiss Ethics Committee Northwest and Central Switzerland (EKNZ, AO_2022–00044). This manuscript is based on protocol V.4.0, 19 January 2024. Trial findings will be disseminated through peer-reviewed publications, conference presentations and through communication offices of the consortium partners and the project’s website (https://tbtriage.com/).Trial registration ClinicalTrials.gov (NCT05526885), South African National Clinical Trials Register (SANCTR; DOH-27-092022-8096).